EVALUATING TOURIST SATISFACTION AND TOURISM SERVICE USING IMPORTANCE AND PERFORMANCE ANALYSIS AT LINOW LAKE, TOMOHON - Sigarlaki, Marel Christian (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Nowadays tourism is one of the common things that important for economics in Indonesia. The challenge facing today by the tourism object is how to make sure the products and services that they provide through the performance in order to achieve the satisfaction of tourist. There are five attributes in tourism service to measuring the tourist satisfaction to their performance, namely: hospitality, attraction, accessibility, infrastructure and environment. The objectives of this research; first, are to know the importance of tourist satisfaction and tourism service. Second, are to know the performance of tourism service and tourist satisfaction at Linow Lake, Tomohon. The method of this research is Importance-Performance Analysis, used to analyze the importance and performance of tourism service to increase the tourist satisfaction on the performance of Linow Lake, Tomohon. The result are: hospitality and infrastructure are located in the quadrant I â€œconcentrate hereâ€ (very important to employees, but performance levels are fairly low); environment is located in quadrant II â€œkeep up the good workâ€ (very important to employees, and at the same time has a high level of performance in this activity); attraction and accessibility are located in the quadrant III â€œlow priorityâ€ (low importance and low performance).Â Keywords: importance-performance analysis, tourism service, tourist satisfaction, hospitality, attraction, accessibility, infrastructure, environment